An Ethnographic Approach of Cancel Culture Against Abidzar in the Indonesian Movie Industry: Production and Consumption Perspective - Sidik, Theola Caesar Aisyah; Sari, Devi Novita; Hamidah, Virgi Senalia; Illaili, Yumna Nisa (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2025)
This paper investigates the dynamics of cancel culture in Indonesia by analyzing the controversy surrounding Abidzar Al-Ghifari’s casting in the Indonesian remake of the Korean drama Business Proposal. Drawing on digital ethnographic methods, the study explores how online K-pop communities engage in the processes of cultural critique and symbolic resistance. Through in-depth interviews with ten fans from digital platforms such as Twitter, Reddit, Telegram, and Facebook, the research examines how both media producers and consumers negotiate aesthetic expectations, moral judgments, and representational legitimacy. The findings show that cancel culture serves not only as a mechanism of social control but also as an arena of participatory discourse where cultural standards, global influences, and national identity are contested. Ultimately, this study highlights how fan communities, empowered by digital connectivity and cultural fluency, have the capacity to influence production decisions and redefine public accountability in the entertainment industry.